Evaluation of criteria for site selection of solar photovoltaic (PV) projects using fuzzy logarithmic additive estimation of weight coefficients. (November 2021) - Deveci, Muhammet; Cali, Umit; Pamucar, Dragan
Abstract: The aim of this study is to determine the degree of importance of criteria affecting site selection of solar photovoltaic (PV) projects using a decision-making model. This study consists of four consecutive stages, as follows: criteria identification, questionnaire (survey), statistical analyses, and degree of importance of criteria. In the first stage, the criteria are determined by reviewing the scientific literature on solar PV projects. Secondly, we conduct a questionnaire to identify the importance of the criteria for solar PV project site selection. We received responses from 33 internationally renowned experts from 22 countries, including academia and industry, using an international evaluation method. Thirdly, statistical analysis is performed in SPSS regarding each criterion, comparing the averages between the groups who filled out the questionnaire. Finally, a novel logarithmic additive estimation of weight coefficients (LAAW) under fuzzy environment is proposed to determine the degree of importance of each criterion for solar PV site selection. The results show that the most important criteria for solar PV site selection are solar radiation, economic performance indicators (net present value (NPV), internal rate of return (IRR), and return on investment (ROI)), carbon emission savings, and policy support. Highlights: Identify the importance of various criteria for the site selection of solar PV projects. A novel decision making approach is proposed. Criteria include technical, economic, environmental, and social/political aspects. The proposed model can be extended to other decision making problems.